Is there any difference in organizational commitment between general hospitals and specialized hospitals? Empirical evidence from public hospitals in Beijing, China - Yirui Gao; Junli Zhu; Lujia Hu; Chen Chen (BMC, 2023)
Abstract Objective The purpose of the study on the one hand is to see different hospital organization commitment have difference, including the overall score and various dimensions, on the other hand, due to the different hospital type, its function orientation is different, the factors of the doctor organization commitment may also exist differences, so the study of another purpose is to determine for different types of hospital doctor organization commitment the focus and key groups, provide reference for the doctor incentive strategy. Methods A total of 292 doctors in four large public hospitals in Beijing were investigated. Physicians' perceived organizational commitment was investigated using self-made electronic questionnaires. Data were analyzed by factor analysis, descriptive statistics, t-test, ANOVA, and multiple linear regression. Results In the large public hospital doctor perception of the hospital commitment status, Specialized hospitals had higher overall commitment behavior scores, it is 3.47 ± 0.86; General hospital commitment behavior scored low at 3.39 ± 0.91. In the regression results, department category, working years, administrative position, and entry mode are the influencing factors of the organizational commitment of doctors in general hospitals, while in specialized hospitals, in addition to whether to hold an administrative position, entry mode, and working hours, the influencing factors also include gender, professional title and overseas learning background. Conclusion There are differences in the perceived organizational commitment by doctors in different types of public hospitals, and different factors influencing their organizational commitment.Hospital type directly influences physicians' organizational commitment and plays a moderating role in influencing other factors. A possible solution is general hospital specialization, encouraging general hospitals to develop the dominant discipline. These findings can help healthcare service hospital executives or government policymakers understand the impact of hospital specialization strategies and develop more efficient medical staff incentive systems.